تأثير تطبيق ابعاد الاستقامة الاستراتيجية في تحقيق التوازن الاستراتيجي/دراسة تحليلية لآراء عينة من العاملين في شركات السفر والسياحة في محافظة النجف. - الماضي ضرغام عبد العالي; الخزعلي معتز حميد رحيم (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
Purpose: The purpose of this research is to evaluate the impact of the dimensions of strategic alignment, which represent the framework for maintaining strategic intent throughout the implementation process regardless of any environmental disruptions that may be encountered during the process, and strategic balance as a balance between existing internal resources and external opportunities. Specifically, this research explores whether there is an impact between strategic alignment and strategic balance. This study is significant for both researchers and institutional leaders as it helps in understanding the relationship between the aforementioned variables. Research Design: The research includes a qualitative analysis of relevant data from a group of travel and tourism companies in Najaf Al-Ashraf. The research sample comprised all employees and leaders in these companies, totaling 125 individuals. Of these, 100 questionnaires were retrieved, and 95 valid questionnaires were subjected to statistical analysis, with 5 being excluded due to their ineligibility for statistical analysis. The analysis is based on a robust foundation aimed at uncovering the practices of these companies in leveraging strategic alignment. The research sought to test several hypotheses related to the impact relationships between the variables, namely strategic alignment and strategic balance. The data was processed using statistical methods through the programs (SmartPLS) and (SPSS). Findings: The findings revealed an impact between strategic alignment and strategic balance. Additionally, the results of the statistical analysis of the data collected through the questionnaire prepared for this purpose, along with theoretical conclusions, demonstrated the companies’ ability to achieve strategic balance by professionally and deliberately dealing with strategic alignment in their plans, which are executed through the concerted efforts of their employees. Contribution/Value: This research contributes as an attempt to reveal the impact of the dimensions of strategic alignment as a modern tool for travel companies in Najaf Al-Ashraf to achieve their strategic balance.